BLOCKCHAIN TECHNOLOGY IN TRAVEL: ENSURING TRUST AND TRANSPARENCY - Shinu Pushpan (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This comprehensive article examines the transformative role of blockchain technology in addressing trust and transparency challenges within the travel industry. The article explores how blockchain solutions are revolutionizing key areas including review verification, booking management, and supply chain transparency. Through case studies of pioneering implementations like Winding Tree and Webjet, the article demonstrates blockchain's capacity to reduce fraudulent activities, streamline operations, and enhance customer trust. The article also investigates how smart contracts automate and secure transactions between travel stakeholders, while analyzing the technology's impact on supplier relationships and service delivery. Additionally, the article examines emerging opportunities in tokenized loyalty programs and decentralized marketplaces, providing insights into the future evolution of blockchain in travel services.